Good Laboratory Practice for optimization research - Kendall, Graham; Bai, Ruibin; Blazewicz, Jacek; De Causmaecker, Patrick; Gendreau, Michel; John, Robert; Li, Jiawei; McCollum, Barry; Pesch, Erwin; Qu, Rong; Sabar, Nasser; Vanden Berghe, Greet; et al. (Palgrave Macmillan, 2016)
Good Laboratory Practice has been a part of non-clinical research for over 40 years yet. Optimization Research, despite having many papers discussing standards being published over the same period of time, has yet to embrace standards that underpin its research. In this paper we argue the need to adopt standards in optimization research. Building on previous papers, many of which have suggested that the optimiza- tion research community should adopt certain standards, we suggest a concrete set of recommendations that the community should adopt. We also discuss how the proposals in this paper could be progressed.